Foreign language acquisition and digital games playing: a focus on vocabulary development - Lorenset, Caroline Chioquetta (2019)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão, Programa de Pós-Graduação em Inglês: Estudos Linguísticos e Literários, Florianópolis, 2019.